PERSEPSI GURU DAN SISWA TENTANG PEMBELAJARAN TATAP MUKA TERBATAS DI MASA PANDEMI COVID-19 - Fahimul Amri; Shanti Nugroho Sulistyowati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the perceptions of teachers and students about limited face-to-face learning (PTMT) during the Covid-19 pandemic. The research described in this article is quantitative descriptive research using the survey method. Respondents of research involved 19 teachers who carried out learning and 49 high school students who participated in limited face-to-face learning in the even semester of 2021/2022. The research instrument used a questionnaire. Data analysis was carried out by using percentage and mean analysis of respondents' answers. The mean analysis was established in the form of a scale range. The results indicated that limited face-to-face learning (PTMT) could be effective, teachers were easy to implement PTMT, and teachers and students preferred PTMT more than online learning. In addition, the results also indicated that PTMT could make a good learning atmosphere, make students involved in the learning activity, make students being passionate or enthusiastic in the learning activity, not make students being lazy during the learning activity, make students focused on learning, make students being more serious in participating while learning process, make students being easier to understand the subject matter, and there was good reciprocal interaction and communication between teachers with students. Teachers and students during the Covid-19 pandemic preferred the learning to be carried out face-to-face, even though it was still limited.